“Gentle” cardio-respiratory management in congenital diaphragmatic hernia: time for a precision-medicine approach? - Foth, Anna; Tingay, David; Kipfmüller, Florian (Seminars in fetal & neonatal medicine, 2025)
Congenital diaphragmatic hernia (CDH) remains one of the most challenging conditions to manage in neonatal intensive care, with outcomes determined by the complex interplay between pulmonary hypoplasia, pulmonary vascular remodeling, and ventricular dysfunction. Traditional treatment strategies, including high-frequency ventilation, inhaled nitric oxide, and vasopressor use, fail to account for the dynamic heterogeneity of CDH physiology and may contribute to persistently high mortality. Emerging evidence delineates three principal hemodynamic phenotypes: (1) preserved biventricular function with mild/no pulmonary hypertension (PH), (2) pre-capillary PH with or without right ventricular dysfunction, and (3) post-capillary PH with primary left ventricular (LV) dysfunction. Each phenotype demands distinct ventilatory and pharmacologic strategies, ranging from cautious respiratory support to targeted pulmonary vasodilators, inodilators, or LV-directed therapies. Ventilation in CDH is further complicated by profound lung inhomogeneity, the “baby lung” phenomenon, and susceptibility to ventilator-induced lung injury. Advances in lung-protective strategies, including low driving pressure, permissive hypercapnia, synchrony-enhancing modes, and real-time functional monitoring with echocardiography, lung ultrasound, electrical impedance tomography, and use of circulating biomarkers enable tailored interventions. A precision medicine approach, grounded in multimodal monitoring and gentle cardiopulmonary support, holds promise to optimize hemodynamic balance, reduce iatrogenic injury, and improve survival and long-term outcomes in infants with CDH.
Online verfügbar: 19. September 2025, Artikelversion: 16. Oktober 2025
Gesehen am 02.12.2025